Parenting Reflected In The Annisa Novel By John Michalsons (2015): A Psychoanalytic Approach - Setiawan, Luqfi Nurul; , Dr.Phil. Dewi Chandraningrum, S.pd, ME.d (2016)
The research is about the story of a girl named Annisa who is the main character in the novel written by John Michaelson. The purpose of this research was to know how psychic condition is the protagonist of this story in the face of the fact that her father made the decision to have a second wife or often called with polygamy, how the main character receives her family's condition was being praised from God, and the reason why the author open issues regarding polygamy which until recently still a very taboo issues to talk about in General. This research was qualitative in nature. The main data in the study is novel Annisa (2015), a brief history of John Michaelson. Secondary data from the research is the ingredients as well as selected references related to study. There are a few conclusions from this research. Polygamy remains the thing that is less acceptable in the perspective of the Islamic community in General, especially in Indonesia where this story takes the location of the settings there. Many of the consequences for someone who is experiencing the problem of polygamy or even for the culprit itself, the views of the community to the person who do polygamy will be so bad as if he just keep his sheer. While for the child in this story, he did not receive at all with what her father did and consider it extremely unreasonable for men in the age of now. The author is trying to convey that the impact of polygamy is not only on the offender but to someone who is near him, because polygamy is still a taboo and law there is no clarity in the community.